Exploring children experience with educational mobile technology - Zuheir N Khlaif; Jamil Itmazi; Shahid Farid; Ali Zuhdi Shaqour; Bochra Kouraïchi (Association for Learning Technology, 2019)
The purpose of this study is to explore and analyse the user experience (UX) of Arabic educational and entertainment applications designed for children aging 8-10 years. This paper reports the results of an experimental study conducted on a sample of 53 children in two elementary schools in Qalqilya and Nablus, Palestine. The context of the current study is different from previous studies that were conducted in a western environment in terms of knowledge, awareness, demographic changes and background variables. Qualitative methods captured the enjoyable and attractive parts of the software being used. The qualitative content analysis showed that participants' enjoyment using the system was quite different. During sessions, children showed much excitement and interest while working with the math app more than the science app. However, girls were less interested to use the math application compared with their use of the device itself. Following Hassenzahl's model, the descriptions of UXs were also categorised into two categories: pragmatic and hedonic; the functionality, technical and ease of use aspects of UX of both the tablet and the math application were categorised as pragmatic. Enjoyable, exciting, confusing and upsetting experiences were categorised as hedonic. Male participants were more familiar with the use of mobile devices than female participants. The results of the present study showed that gender, culture and religion are important factors that affect children's experience to use new technological devices since three female participants were reluctant to use the tablet especially due to cultural and religious factors.